Dealing with AIDS in the workplace : guidelines for managers and supervisors : what you need to know (The Confederation St MichaelBB, 2001)
Provides direction in instituting programmes consistent with applicable laws covering education, labour management and personnel policies for employees who have been confirmed positive for HIV and/or have disability from the manifestation of AIDS.
Keywords: AIDS